MEASUREMENT SCALES AND OPTIMIZATION IN ECONOMICS - Donald W. Katzner (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
This paper explores the impact on the outcome of optimizing a function when permissible transformations of the scale of measurement are applied to the variable with respect to which that function is optimized. The collection of permissible transformations vary depending on whether the variable is measured on a ratio, cardinal (interval), or ordinal scale. Certain problems arise when the variable in question is measured only on an ordinal scale.